Discovering protective CD8 T cell epitopes—no single immunologic property predicts it!. (June 2015) - Gilchuk, Pavlo; Hill, Timothy M; Wilson, John T; Joyce, Sebastian
Highlights: Numerous microbial determinants are presented by MHC class I molecules during a natural infection. Immune CD8 T cells recognize only a small subset of such determinants. Naturally processed, immunogenic epitopes inform vaccine candidates. Neither immunogenicity nor immunodominance predicts protection. Protective T cell epitopes need to be empirically determined. Abstract : Once a burgeoning field of study, over the past decade or so, T cell epitope discovery has lost some luster. The contributory factors perchance are the general notion that any newly discovered epitope will reveal very little about an immune response and that knowledge of epitopes are less critical for vaccine design. Despite these notions, the breadth and depth of T cell epitopes derived from clinically important microbial agents of human diseases largely remain ill defined. We review here a flurry of recent reports that have rebirthed the field. These reports reveal that epitope discovery is an essential step toward rational vaccine design and critical for monitoring vaccination efficacy. The new findings also indicate that neither immunogenicity nor immunodominance predict protective immunity. Hence, an immunogenic epitope is but a peptide unless proven protective against disease.